Cirugía renal percutánea: nefroscopia. - Corral Rosillo, J.; Chicharro Almarza, J.; Esteban Fuertes, M.; Luengo Alpuente, S.; Mohamed Mohamed-abdallah, Z.; Resel, Luis; Silmi Moyano, A. (Clínicas Urológicas de la Complutense, 1994)
Sin resumen